Wet-suction versus slow-pull technique for endoscopic ultrasound-guided fine-needle biopsy: a multicenter, randomized, crossover trial - Crinò, Stefano Francesco; Conti Bellocchi, Maria Cristina; Di Mitri, Roberto; Inzani, Frediano; Rimbaș, Mihai; Lisotti, Andrea; Manfredi, Guido; Teoh, Anthony Y. B.; Mangiavillano, Benedetto; Sendino, Oriol; Bernardoni, Laura; Manfrin, Erminia; Scimeca, Daniela; Unti, Elettra; Carlino, Angela; Voiosu, Theodor; Mateescu, R. Bogdan; Fusaroli, Pietro; Lega, Stefania; Buscarini, Elisabetta; Pergola, Lorena; Chan, Shannon M.; Lamonaca, Laura; Ginès, Àngels; Fernández-Esparrach, Gloria; Facciorusso, Antonio; Larghi, Alberto (Endoscopy, 2022)
Background It is unknown whether there is an advantage to using the wet-suction or slow-pull technique during endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) with new-generation needles. We aimed to compare the performance of each technique in EUS-FNB.Methods This was a multicenter, randomized, single-blind, crossover trial including patients with solid lesions of ≥ 1 cm. Four needle passes with 22 G fork-tip or Franseen-type needles were performed, alternating the wet-suction and slow-pull techniques in a randomized order. The primary outcome was the histological yield (samples containing an intact piece of tissue of at least 550 μm). Secondary end points were sample quality (tissue integrity and blood contamination), diagnostic accuracy, and adequate tumor fraction.Results Overall, 210 patients with 146 pancreatic and 64 nonpancreatic lesions were analyzed. A tissue core was retrieved in 150 (71.4 %) and 129 (61.4 %) cases using the wet-suction and the slow-pull techniques, respectively (P = 0.03). The mean tissue integrity score was higher using wet suction (P = 0.02), as was the blood contamination of samples (P < 0.001). In the two subgroups of pancreatic and nonpancreatic lesions, tissue core rate and tissue integrity score were not statistically different using the two techniques, but blood contamination was higher with wet suction. Diagnostic accuracy and tumor fraction did not differ between the two techniques.Conclusion Overall, the wet-suction technique in EUS-FNB resulted in a higher tissue core procurement rate compared with the slow-pull method. Diagnostic accuracy and the rate of samples with adequate tumor fraction were similar between the two techniques.